ANALISIS ARUS TRANSIEN PADA SISI PRIMER TRANSFORMATOR TERHADAP PELEPASAN BEBAN MENGGUNAKAN SIMULASI EMTP - Arfita Yuana Dewi (Teknoin, 2006)
Transient phenomena can be happened at electrical equipment, like primary side of transformer, transmission circuit, generator, etc. This condition caused by external or internal trouble of equipment, like short circuit, switching equipment. This condition can be happened in short time and it has big magnitude value, then it will effect to electrical equipment. If the transformer has short circuit trouble, switching trouble, big current will flow to transformer circuit.         This research will count the current transient value at primary side of transformer, by using EMTP (Electromagnetic Transient Program).        Based on the simulation to 21,5 MVA transformer,  1241 A nominal current, this research have result that over load value more than 22,5 MVA will have 1243 A current transient. This value is more than nominal current value of primary side, it caused by, if load have big value and primary current have big value too.Keywords: wool fiber, acrylic, blending process